IMPROVEMENT OF IPS LEARNING ACTIVITY AND OUTCOMES THROUGH THE TIME TOKEN ARENDS MODEL - Fadil Fadillah (JURNAL SOCIUS, 2021)
A social science teacher is required to apply an effective model so that it can arouse students' learning interest so that the objectives to be achieved can be fulfilled. To be able to create effective and efficient learning, teachers must have the ability to master teaching materials, manage classes and be able to place appropriate models during the teaching and learning process. One strategy that can be used to overcome problems in learning social science is the Time Token Arends model. The object of this study is students of Class VIII MTs Darul Ulum Kotabaru and the selected class is students of Class VIII A MTs Darul Ulum Kotabaru with a total of 32 students. This research uses a qualitative approach. The results of the study of the variables studied will be described qualitatively with the variable implementation of the Time Token Arends learning model, student learning outcomes, and student activity levels. The results of this study are the conclusion that the use of the Time Token Arends model can increase teacher activity, student activity, and student learning outcomes.